2014
DOI: 10.1098/rstb.2013.0482
|View full text |Cite
|
Sign up to set email alerts
|

Habits as action sequences: hierarchical action control and changes in outcome value

Abstract: One contribution of 18 to a Theme Issue 'The principles of goal-directed decisionmaking: from neural mechanisms to computation and robotics'. Goal-directed action involves making high-level choices that are implemented using previously acquired action sequences to attain desired goals. Such a hierarchical schema is necessary for goal-directed actions to be scalable to real-life situations, but results in decision-making that is less flexible than when action sequences are unfolded and the decision-maker delibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
118
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(133 citation statements)
references
References 54 publications
7
118
0
Order By: Relevance
“…Automating behavior is a way to optimize benefit from an environment. Thus situations (e.g., stimuli) associated with actions that have consistently led to reinforcement eventually come to release appropriate action chains (Adams 1982;Daw et al 2006;Dezfouli et al 2014; These stimulus-action associations are cached and controlled by sensorimotor circuits in the basal ganglia, such as the aDLS (Everitt and Robbins 2013;Graybiel 1998Graybiel , 2008Miyachi et al 2002;Packard and McGaugh 1996;Yin and Knowlton 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Automating behavior is a way to optimize benefit from an environment. Thus situations (e.g., stimuli) associated with actions that have consistently led to reinforcement eventually come to release appropriate action chains (Adams 1982;Daw et al 2006;Dezfouli et al 2014; These stimulus-action associations are cached and controlled by sensorimotor circuits in the basal ganglia, such as the aDLS (Everitt and Robbins 2013;Graybiel 1998Graybiel , 2008Miyachi et al 2002;Packard and McGaugh 1996;Yin and Knowlton 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in stable environments, as actions become more automated (e.g., habit based), control shifts to sensorimotor circuits capable of encoding action chains (Dezfouli et al 2014;Graybiel 2008;Yin and Knowlton 2006), which include the aDLS (Alexander and Crutcher 1990;Berendse et al 1992;Carrelli and West 1991;McGeorge and Faull 1989). Graybiel and colleagues have reported that the development of these action chains on a cued T-maze aligns with the development of preferential firing in dorsolateral striatum at the beginning and end of their T-maze (task bracketing; Barnes et al 2005;Jog et al 1999;Smith and Graybiel 2013;Thorn et al 2010).…”
mentioning
confidence: 99%
“…Thus, the MF prediction arises from learning from past encounters of state x to minimize untoward inconsistencies. Even more extreme MF systems directly couple observations to decisions, for instance using the inconsistencies to learn appropriate actions or action sequences [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Habits are learned behavioral patterns that are performed without much conscious deliberation and instead strongly controlled by the stimulus environment (Dezfouli et al 2014;Orbell and Verplanken 2015). Indeed, actions such as turning the light on/off, disposing waste, running the bath or shower are often done in a repetitive and almost unconscious way.…”
Section: The Influence Of Habits and Environmental Stimulimentioning
confidence: 99%